2006
DOI: 10.1007/s10067-005-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Partial construction of apoptotic pathway in PBMC obtained from active SLE patients and the significance of plasma TNF-α on this pathway

Abstract: Systemic lupus erythematosus (SLE) is a complex autoimmune disorder that affects various organs and systems. Increased apoptosis, together with defects in the uptake of apoptotic bodies, are thought to have a pathogenic role in SLE. By detection of chromatin condensation, 30% of apoptosis was detected in peripheral blood mononuclear cells (PBMC) from Thai patients with active SLE. Therefore, understanding of the molecular processes in PBMC apoptosis may allow us to gain insight into pathophysiology of SLE. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…DHF plasma samples containing TNF‐α at a concentration ≥ 20 pg/ml were selected for the apoptotic induction experiment, as previously described (20). Briefly, 3 × 10 6 PBMCs from healthy donors were pre‐incubated with 100 μl DHF plasma in the presence or absence of 20 pg etanercept, an anti‐TNF‐α antibody (Wyeth, Philadelphia, PA, USA), at 37°C for 2 hr.…”
Section: Methodsmentioning
confidence: 99%
“…DHF plasma samples containing TNF‐α at a concentration ≥ 20 pg/ml were selected for the apoptotic induction experiment, as previously described (20). Briefly, 3 × 10 6 PBMCs from healthy donors were pre‐incubated with 100 μl DHF plasma in the presence or absence of 20 pg etanercept, an anti‐TNF‐α antibody (Wyeth, Philadelphia, PA, USA), at 37°C for 2 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, transglutaminase 2 (TG2) has been implicated in the pathogenesis of SLE [Szondy et al, 2003; Pitidhammabhorn et al, 2006]. TG2 is known as a multi‐functional enzyme that is expressed in the majority of tissues and implicated in numerous biological functions, including remodeling of the extracellular matrix [Aeschlimann et al, 1995], stimulus‐secretion coupling [Bungay et al, 1986], receptor‐mediated endocytosis [Davies et al, 1980], cell differentiation [Aeschlimann et al, 1993], tumor growth [Johnson et al, 1994], and apoptosis [Fesus et al, 1987].…”
mentioning
confidence: 99%
“…Recent reports from human studies have also directly or indirectly indicated upregulation of many of these pathways including NF-kB (58); death receptor signaling (59); integrin signaling (60); IL-4 signaling (61), PDGF signaling (62); and Glucocorticoid receptor signaling (63). …”
Section: Discussionmentioning
confidence: 99%